Instruments Measuring Self-Care in Children and Young Adults With Chronic Conditions: A Systematic Review - Biagioli, Valentina; Spitaletta, Giuseppina; Kania, Valeria; Mascolo, Rachele; Gawronski, Orsola; Liburdi, Annachiara; Manzi, Giulia; Salata, Michele; Vellone, Ercole; Tiozzo, Emanuela; Dall’Oglio, Immacolata (Frontiers in Pediatrics, 2022)
Children and young adults (CYAs) with chronic conditions need to engage in self-care to improve their quality of life. This study aimed to retrieve the literature on instruments to assess self-care in CYAs living with chronic conditions and evaluate the psychometric proprieties of the instruments retrieved. A systematic literature review was conducted on six databases to identify peer-reviewed papers that described or used an evaluation instrument of self-care in CYAs with chronic conditions. Twenty-three articles describing eleven instruments of self-care were identified. Five instruments (45.45%) were developed for specific diseases, while six (54.54%) for various chronic illnesses. Most of the instruments were focused on treatment adherence within self-care maintenance (i.e., behaviors to maintain illness stability), excluding the monitoring of clinical parameters or the management of exacerbations. This review provides an overview of available instruments that measure self-care in CYAs with chronic conditions, which health professionals could use for patient education.